The Effect of Macroeconomic Variables On Stock Returns on Dhaka Stock Exchange - Quadir, Muhammed Monjurul (International Journal of Economics and Financial Issues, 2012)
This article investigates the effects of macroeconomic variables of treasury bill interest rate and industrial production on stock returns on Dhaka Stock Exchange for the period between January 2000 and February 2007 on the basis of monthly time series data using Autoregressive Integrated Moving Average (ARIMA) model. The paper has taken the overall market stock returns as an independent variable. It does not consider the stock returns of different companies separately. Though the ARIMA model finds a positive relationship between Treasury bill interest rate and industrial production with market stock returns but the coefficients have turned out to be statistically insignificant. Keywords: Stock Returns; Macroeconomic Variables; Autoregressive Integrated Moving Average. JEL Classifications: D11; E32; E37; G12; G32